Viscoelastic negative stiffness metamaterial with multistage load bearing and programmable energy absorption ability - Tianzhen Liu; Cheng Lin; Yonglin Zhang; Jianguo Cai; Jinglei Yang (International Journal of Smart and Nano Materials)
The mechanical properties of negative stiffness (NS) metamaterial could be customized and tuned in a wide range for various requirements, achieving programmable performances by the design from the aspect of structure and material. This work investigates the viscoelastic NS metamaterial based on double curved beams using a combined approach of experiments, simulations, and analytical modeling with an emphasis on multistage loading bearing and programmable energy absorption ability. Numerical simulations are first implemented based on the finite element models of three types of metamaterial cells, which provide comparisons of load bearing and energy absorption properties. Further, the effects of geometric parameters of multistage metamaterial element and the mechanisms are analyzed. An analytical discrete model is then innovatively developed to provide straightforward understandings of the geometric effects and reveal the role of viscoelasticity by examining the instantaneous loading responses and rate-dependent behaviors. Experimentally, we fabricate the metamaterial samples using 3D-printing technique and perform compression tests to validate the properties based on different boundary conditions, loading rates and cyclic loading and unloading. Results of this work show the potential of wide programmable room for mechanical properties through structure and functional material design, such as multistage load bearing capacity and energy absorption ability.